ANALISIS PENGUKURAN PARTIKULAT KUALITAS UDARA OUTDOOR DI KAMPUS PSDKU UNIVERSITAS AIRLANGGA DI BANYUWANGI: Analysis Of Outdoor Air Quality Particulate Measurement At Airlangga University PSDKU Campus In Banyuwangi - Aghisni Isfiya; Griselda Malinda E. P; Widatul Mila; Septa Puspikawati (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2020)
Air pollution can be interpreted as the presence of foreign substance or level substance contained in the air, so that it can cause changes in the composition of the air from normal conditions. The presence of pollutants sourced from moving and immovable sources can be in the form of dust particles that can affect the level of air quality in the environment and interfere with human health, so that air quality is measured. The measurement of air quality particulates carried out aims to determine the quality of outdoor air at PSDKU Airlangga University in Banyuwangi. This type of research is descriptive observational research. The method used in sampling is purposive sampling. This research was conducted in 5 locations, namely Sobo basketball court, student parking lot, outdoor student discussion area I, Sobo campus outdoor canteen, and outdoor student discussion area II. The result of measurements of dust particulate levels showed that all places were in the good category, but the student parking lot had the highest average which is equal to 1,572 Âµ/m3, compared to the other 4 places. Efforts that can be made to overcome the high levels of dust particulates in PSDKU Airlangga University in Banyuwangi include reducing the use of motorized vehicles, as well as always covering the helmet and wearing masks when driving, as well as care free day policies in the campus area.